Definition of a microbial signature as a predictor of endoscopic post-surgical recurrence in patients with Crohn’s disease - Oliver, Lia; Camps, Blau; Julià-Bergkvist, David; Amoedo, Joan; Ramió-Pujol, Sara; Malagón, Marta; Bahí, Anna; Torres, Paola; Domènech, Eugeni; Guardiola, Jordi; Serra-Pagès, Mariona; Garcia-Gil, Jesus; et al. (Frontiers in Molecular Medicine, 2023)
Background and aimsAlthough there are several effective drugs for the treatment of Crohn's disease (CD), almost 70% of patients will end up needing a surgical resection throughout their lives. This procedure is not always curative, as endoscopic recurrence occurs in 65%-90% of patients after one year from surgery. The aetiology of the recurrence is unknown; however, several studies have shown how the resident microbiota is modified after surgery. The aim of this study is to evaluate samples from patients with CD before and after an intestinal resection to determine if at baseline there are differences in the abundance of different microbial markers, which could be capable of predicting endoscopic recurrences. Methods In this observational study, a stool sample was obtained from 25 patients with CD before undergoing surgery, recruited at 3 Catalan hospitals. From each sample, DNA was purified and the relative abundance of 9 microbial markers was quantified using qPCR. Results An algorithm composed of 4 microbial markers (E. coli, F. prausnitzii phylogroup I, Bacteroidetes, and Eubacteria) shows a sensitivity and specificity of 90.91% and 85.71%, respectively, and a positive and negative predictive value of 83.33% and 92.31%, respectively. Conclusions A microbial signature to determine patients who will have post-surgical recurrence has been identified. This tool can be very useful in daily clinical practice allowing to schedule a personalized therapy, enabling preventive treatment only in that subgroup of patients who really require it.